Structural-Semantic Study Of Civil Architecture And Military Architecture Of Khorezm In The Uzbek And Russian Languages. - Shamsutdinova Galiya Shamilevna (Euro Asian Journal Publishing, 2024)
Khorezm, an ancient territory located in present-day Uzbekistan, has a rich architectural heritage that reflects the historical, cultural, and social complexity of the region. The monumental heritage of Khmer Rouge includes a variety of civil and military buildings, each with its own stylistic elements, functional characteristics, and symbolic meanings. By conducting a structural and semantic study of Khmer Rouge civil architecture and military architecture in Uzbek and Russian, this study aims to study linguistic images and conceptual foundations associated with these forms of architecture
Keywords: Khorezm region; civil architecture; military architecture